2019
DOI: 10.1021/jacs.9b00147
|View full text |Cite
|
Sign up to set email alerts
|

Upgraded Bioelectrocatalytic N2 Fixation: From N2 to Chiral Amine Intermediates

Abstract: Enantiomerically pure chiral amines are of increasing value in the preparation of bioactive compounds, pharmaceuticals, and agrochemicals. ω-Transaminase (ω-TA) is an ideal catalyst for asymmetric amination because of its excellent enantioselectivity and wide substrate scope. To shift the equilibrium of reactions catalyzed by ω-TA to the side of the amine product, an upgraded N2 fixation system based on bioelectrocatalysis was developed to realize the conversion from N2 to chiral amine intermediates. The produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 50 publications
0
72
0
2
Order By: Relevance
“…To this end, the Minteer group has extended the use of reduced MV in bioelectrosynthetic cells to reduce NADH. In this way, the NH 3 formed by nitrogenase can be upgraded to further products of interest, such as chiral amines and chiral amino acids [155,156].…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…To this end, the Minteer group has extended the use of reduced MV in bioelectrosynthetic cells to reduce NADH. In this way, the NH 3 formed by nitrogenase can be upgraded to further products of interest, such as chiral amines and chiral amino acids [155,156].…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Recent research has also capitalized on electrocatalytic N 2 fixation with the Fe and MoFe proteins, although the produced NH 3 is further upgraded in a cascade that employs a total of five enzymes: Fe protein, MoFe protein, diaphorase, L‐alanine dehydrogenase and ω‐transaminase (Figure ). In this way, the Minteer group demonstrated that chiral amines (such as (R)‐1‐methyl‐3‐phenylpropylamine) could be produced where reduced MV was used to fix N 2 with nitrogenase as well as to produce reduced nicotinamide adenine dinucleotide (NADH), required for L‐alanine dehydrogenase . This concept was recently upgraded further to a system in which a H 2 ase‐based H 2 ‐oxidizing anode was coupled to a nitrogenase‐based cathode for N 2 reduction to NH 3 (dependent on ATP hydrolysis); the produced NH 3 was subsequently coupled with diaphorase and leucine dehydrogenase to perform asymmetric α‐keto acid aminations forming chiral amino acids with high FEs and enantiomeric excess .…”
Section: Recent Examples Of Enzymatic Electrochemistry For Small Molementioning
confidence: 99%
“…There are mainly two types of bioelectrosynthetic systems: a fuel-cell-type [142,[144][145][146][147][148][149] and an electrolysis-type [28,53,141,143,[150][151][152][153][154]. The former realizes a spontaneous production of compounds without any external power supplies, whereas the latter proceeds relatively rapid reactions due to an optimally controlled electrode potential to realize diffusion-controlled conditions.…”
Section: Bioelectrosynthesismentioning
confidence: 99%
“…On the other hand, reductive production of chiral compounds is useful in many cases. Minteer's group reported various NAD + -dependent multienzymatic cascade reactions for generating chiral compounds, as shown in Figure 5 [149,152,153].…”
Section: Nad(p) + -Dependent Bioelectrosynthesismentioning
confidence: 99%